Guided by principles or rules: a Delphi study on how safety professionals frame safety practices - Pilbeam, Colin; Denyer, David; Sutliff, Mike (Elsevier, 2025)
This study explores how safety professionals conceptualize and articulate safety practices, examining how their framing influences actions, facilitates learning from failures, and impacts overall safety outcomes. Twenty-nine safety professionals participated in a Delphi study, which included three online workshops and three rounds of surveys. Eighteen safety practices were developed, framed as both rules-based and principles-based practices. Survey results indicated that both rules-based and principles-based practices were considered essential for achieving safety, with their relative balance likely being context-dependent. While all practices were considered important for preventing accidents, those framed as principles were seen as more challenging to implement but ultimately more effective, especially in complex situations. Better understanding of the way in which safety practices are framed has significant implications for the development of safety standards, guidelines, and recommendations.
Keywords: Human Factors; 40 Engineering; 42 Health sciences; 52 Psychology